Improving Blueberry Fruit Nutritional Quality through Physiological and Genetic Interventions: A Review of Current Research and Future Directions - Priti Krishna; Gareema Pandey; Richard Thomas; Sophie Parks (MDPI AG, 2023)
Blueberry, hailed as an antioxidant superfood, is the fruit of small shrubs in the genus Vaccinium (family Ericaceae). The fruits are a rich source of vitamins, minerals and antioxidants such as flavonoids and phenolic acids. The antioxidative and anti-inflammatory activities derived from the polyphenolic compounds, particularly from the abundantly present anthocyanin pigment, have been highlighted as the major contributing factor to the health-benefitting properties of blueberry. In recent years, blueberry cultivation under polytunnels has expanded, with plastic covers designed to offer protection of crop and fruit yield from suboptimal environmental conditions and birds. An important consideration is that the covers reduce photosynthetically active radiation (PAR) and filter out ultraviolet (UV) radiation that is critical for the fruit's bioactive composition. Blueberry fruits grown under covers have been reported to have reduced antioxidant capacity as compared to fruits from open fields. In addition to light, abiotic stresses such as salinity, water deficit, and low temperature trigger accumulation of antioxidants. We highlight in this review how interventions such as light-emitting diodes (LEDs), photo-selective films, and exposure of plants to mild stresses, alongside developing new varieties with desired traits, could be used to optimise the nutritional quality, particularly the content of polyphenols, of blueberry grown under covers.